Mollusk communities of the central Congo River shaped by combined effects of barriers, environmental gradients, and species dispersal - Wembo Ndeo, Oscar; Hauffe, Torsten; Delicado, Diana; Kankonda Busanga, Alidor; Albrecht, Christian; Justus Liebig University Giessen (My University, 2017)
Rapids, falls, and cascades might act as barriers for freshwater species, determining the species community up- and downstream of barriers. However, they affect community composition not only by acting as barriers but also by their influence on environmental gradients. Moreover, the directional dispersal of species along the watercourse might determine community composition. A suitable system to study these differential effects is the Congo River, the world s second largest river by discharge. The small Upper Congo Rapids ecoregion features several rapids known as barrier for fish. The Wagenia Cataract at the town of Kisangani constitutes the strongest drop of the Congo River and several studies have emphasized its role as barrier for fish distribution. Alternative explanations for this pattern, however, are rarely evaluated. Though mollusks represent a vital component of the macrozoobenthos, with distribution patterns and underlying drivers often distinct from that of fishes, virtually no field surveys of the Congo River have been reported for decades. We collected and determined mollusks of 51 stations, recorded environmental conditions, and generated proxies for directional species dispersal and an indirect barrier effect. Those variables were subjected to distance-based redundancy analyses and variation partitioning in order to test whether the mollusk community compositions are better explained by an individual or combined influence of the direct and indirect effect of the cataract barrier, environmental conditions, and downstreamdirected dispersal. Our survey showed an exclusive upstream/downstream distribution for just four out of the 19 species, suggesting a limited barrier effect. We revealed no direct influence of the barrier itself on community composition but of substrate type. However, we found an indirect effect of the barrier through replacing spatially structured communities upstream of the cataract with more uniform ones downstream. Downstream-directed dispersal explained the highest fraction of variation in mollusk communities. Thus, environmental factors, the indirect cataract effect, and downstream-directed spatial proxies model mollusk community composition in concert. These results support previous studies showing a multi-factorial imprint on communities. However, a large fraction of variation community composition remained unexplained, potentially due to flood plain dynamics that (re-)shape mollusk communities constantly and a high temporal turnover, evidenced by the comparison with historical surveys. This is likely caused by the growth of Kisangani and resulting human activities. A monitoring system could allow better assessments of these impacts on communities and the conservation status of endemic species in the Wagenia Cataract.
Keywords: ddc:570